THE IMPACT OF FOOD QUALITY, SERVICE QUALITY, AND PHYSICAL ENVIRONMENT TOWARD CUSTOMER SATISFACTION ON KFC - Amir, Annisa Maharani (Jurnal Ilmiah Mahasiswa FEB, 2021)
As the competitions among FFR businesses are inevitable, to comprehend the factors associated with the successful of KFC as the leader of the market based on the dimension of dining experience attribute to customer satisfaction, this research is conducted. This research aimed to investigate the impact of Food Quality (X1), Service Quality (X2), and Physical Environment (X3) toward Customer Satisfaction (Y) in KFC in Indonesia. This research used a quantitative method to analyze the effect between the independent and dependent variables. The samples were taken from purposive sampling, consisting of 250 of KFC customers who had visited the restaurant within the past year. The questionnaire was used as the research instrument to collect the primary data. This research is supported by previous study as well to support the result. The data were collected by SPSS and PLS application. The results of this research indicate that Food Quality (X1), Service Quality (X2), and Physical Environment (X3) have a significant impact as well on Customer Satisfaction (Y). Hence, it is important to maintain those variables to the standard quality as those have a significant impact toward customer satisfaction.Keywords: Food quality, service quality, physical environment, customer satisfaction, fast-food restaurant.